SOEP-IS 2016 - HGEN: Household-related status and generated variables - DIW Berlin / SOEP (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Variables in the file hgen documented here are generated mostly from the answers in the household questionnaire. There is one row for each wave (syear) a household (hid) participated in the survey.
Keywords: 330